Mismatched ligand density enables ordered assembly of mixed-dimensional, cross-species materials - Li, Tongtao (2023)
The ordered coassembly of mixed-dimensional species-such as zero-dimensional (0D) nanocrystals and 2D microscale nanosheets-is commonly deemed impracticable, as phase separation almost invariably occurs. Here, by manipulating the ligand grafting density, we achieve ordered coassembly of 0D nanocrystals and 2D nanosheets under standard solvent evaporation conditions, resulting in macroscopic, freestanding hybrid-dimensional superlattices with both out-of-plane and in-plane order. The key to suppressing the notorious phase separation lies in hydrophobizing nanosheets with molecular ligands identical to those of nanocrystals but having substantially lower grafting density. The mismatched ligand density endows the two mixed-dimensional components with a molecular recognition-like capability, driving the spontaneous organization of densely capped nanocrystals at the interlayers of sparsely grafted nanosheets. Theoretical calculations reveal that the intercalation of nanocrystals can substantially reduce the short-range repulsions of ligand-grafted nanosheets and is therefore energetically favorable, while subsequent ligand-ligand van der Waals attractions induce the in-plane order and kinetically stabilize the laminate superlattice structure.